Question
upstudy study bank question image url

\( 2.2 e^{x}-(3+e)=-3 e^{1-x} \) 3 Find the first four terms in the Binomial expansion of \( \frac{1}{\left(\frac{1}{\ln e}+e^{\ln (-3 x)}\right)^{2}} \)

Ask by Guerrero Ortega. in South Africa
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The first four terms in the Binomial expansion are \(1 + 6x + 27x² + 108x³\).

Solution

We wish to expand   1   ————————————   [1/ln(e) + e^(ln(–3x)]² step‐by‐step. Step 1. Simplify the expression under the square. Notice that ln(e) = 1 so that   1/ln(e) = 1. Also, e^(ln(–3x)) = –3x (provided –3x is within the domain of the logarithm). Thus, the expression becomes   1/[(1 – 3x)²]  or  (1 – 3x)^(–2). Step 2. Find the Binomial expansion of (1 – 3x)^(–2). Recall the general binomial expansion for a power –k:   (1 + t)^(–k) = Σ [n=0 to ∞] (n+k–1 choose n)·(t)ⁿ for |t| < 1. Here, we set k = 2 and let t = –3x. However, it is actually simpler to use the well‐known expansion:   (1 – u)^(–2) = Σ [n=0 to ∞] (n + 1) uⁿ    (for |u| < 1). In our problem u = 3x (note that the original expression is (1 – 3x); the minus sign is already “built in” to the binomial form). Thus,   (1 – 3x)^(–2) = Σ [n=0 to ∞] (n + 1) (3x)ⁿ. Step 3. Write the first four terms of the expansion. For n = 0:  Term₀ = (0 + 1)·(3x)⁰ = 1 For n = 1:  Term₁ = (1 + 1)·(3x)¹ = 2·3x = 6x For n = 2:  Term₂ = (2 + 1)·(3x)² = 3·9x² = 27x² For n = 3:  Term₃ = (3 + 1)·(3x)³ = 4·27x³ = 108x³ Step 4. Write your final answer. The first four terms in the expansion of   1/[(1/ln e + e^(ln(–3x))]² are   1 + 6x + 27x² + 108x³. Remember, this expansion is valid for |3x| < 1, i.e. |x| < 1/3.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \( 2.2 e^{x}-(3+e)=-3 e^{1-x} \), we first rearrange it to isolate terms involving \( e^x \). This simplifies to \( 2.2 e^{x} + 3 e^{1-x} = 3 + e \). Next, we can substitute \( e^{1-x} = \frac{e}{e^x} \) to make it easier to work with. Once we find \( x \), we can use that in the second part. Now, for the binomial expansion of \( \frac{1}{\left(\frac{1}{\ln e} + e^{\ln (-3x)}\right)^{2}} \), note that \( e^{\ln (-3x)} = -3x \) using the property of logarithms. So we essentially want to expand \( \frac{1}{\left(1 + (-3x)\right)^{2}} \). Utilizing the binomial series, we can write: \[ \frac{1}{(1 - 3x)^{2}} = \sum_{n=0}^{\infty} \binom{n+1}{1} (3x)^n \] The first four terms would be: 1. \( \binom{1}{1}(3x)^0 = 1 \) 2. \( \binom{2}{1}(3x)^1 = 6x \) 3. \( \binom{3}{1}(3x)^2 = 27x^2 \) 4. \( \binom{4}{1}(3x)^3 = 108x^3 \) Thus, the first four terms are \( 1 + 6x + 27x^2 + 108x^3 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy